Balancing the property right of forest owners and the right to healthy environment in Latvia - Seilis, Rūdolfs (Riga Graduate School of Law, 2020)
Strong and reliable right in property has not only been one of the cornerstones of a democratic capitalistic society, but also the provider of confidence for development in forest investment and sustainable management. Being a fundamental human right, right to property is also frequently recognised in constitutions, including the Constitution of the Republic of Latvia under Article 105. Even though the right to healthy environment is not universally accepted, the emergence and expansion of the concept of sustainable development has led to a broader base of stakeholders in forest properties. With a convincingly growing confidence it has been repeatedly stated by both legislators and judicial bodies, that social, economic and environmental rights must be viewed interconnectedly. This paper analyses various written sources to examine the regional legal obligations and current practice in setting up nature preservation areas in Latvia, considering international practice and environmental policy instruments. The research concludes that policy implementation process should be enhanced in Latvia by firmly combining forest management planning with the environemental planning, while also affording a higher degree of participation of forest owners in the protected site designation process. The current compensation mechanism for limiting the property right is considered and propositions for improvement are made. The need to develop a standard for assessing the degree of impact on stakeholder rights is enhanced. Potential improvements in current compensation mechanisms are discussed, while additional incentives should be provided to facilitate self-regulation in Latvia.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::Environmental law; Forests; Latvia